Introduction of manuscripts of Sheikh Maruf Nodehi and Kak Ahmad Sheikh in Iranian libraries - tailor, The caravan of Osman the (Sulaimani Journal for Humanities, 2024)
Sheikh Marufi Nodehi was born in 1166 AH. Q. He was born in the village of Nodehi in the Sharbazh district and died in 1254. He has left nearly 40 works. His son, Kak Ahmad Sheikh, was also a poet. 66 copies of various works of Sheikh Maruf and 14 copies of Kak Ahmad Sheikh's works are kept in different libraries of Iran. We have introduced the details and location of these works. Sheikh Maruf has a collection of poems in 28 verses. The rhyme of each verse in these poems is arranged based on the letters of the Persian alphabet. We have corrected these poems based on manuscript number 55202 of the Razavi Shrine Library. Kak Ahmad Sheikh also has a poem in Kurdish, which we have corrected based on version number 7816 of the library of the Islamic Consultative Assembly of Iran.
Keywords: Sheikh Maruf Nodehi; Kak Ahmad Sheikh; Critical Correction; Kurdish Poem